Análise da diversidade genética dos Afídeos Schizaphis graminum (Rondani) e Metopolophium dirhodum (Walker)(Hemiptera: Aphididae) - Silva, Marcelo Lopes da (2005)
Orientador : Luiz Gonzaga Esteves Vieira